The global landscape of availability, accessibility and affordability of essential diagnostics and therapeutics for the management of HER2-positive breast cancer: The ONCOLLEGE-001 survey. (June 2021) - Trapani, D.; Lengyel, C.G.; Habeeb, B.S.; Altuna, S.C.; Petrillo, A.; El Bairi, K.; Hussain, S.; Mazher, S.A.; Elfaham, E.M.; Curigliano, G.; Khan, S.Z.
Highlights: Impaired access to quality essential diagnostics (ED) and medicines (EM) is a major barrier to cancer care. ONCOLLEGE-001 is the first global survey on the availability of HER2 EDs and EMs for breast cancer. Affordable access to EDs and EMs in the public sector is modest, especially in low- and middle- income countries. Unaffordability is the principal barrier for patients to receive quality cancer care, affected by health insurance schemes and reimbursement policies. Policy solutions to optimize the efficiency in the selection and prioritization of EMs and EDs are urgently needed. Abstract: Aim of the Study: Barriers in access to essential care are key determinants of disparities in cancer survival. Breast cancer (BC) is the most common cancer and lead cause of mortality among women, 60 % occurring in low- and middle-income countries (LMs). A quarter of BC are characterized by an over-expression of the epidermal growth factor receptor 2 (HER2). Valuable strategies to diagnose and manage patients with HER2-positive BC have been determined and some considered essential health interventions. ONCOLLEGE-001 is a global survey of availability, accessibility, and affordability of essential HER2 diagnostics and therapeutics. Method: A self-administered questionnaire was shared electronically to oncologists, identified from oncology networks. Data were analyzed using descriptive statistics, per income areas and geographic regions. Results: We received 191 responses (84 % response rate). The majority of the responders were from LMs (n = 153) and were physician providers. Immunohistochemistry was the most common HER2 diagnostics available (n = 185). A third of the responders from low/lower-middle and a half of upper-middle income countries had HER2 testing only in the private sector. Trastuzumab was not available for 8 %: when available, 15%–21% reported accessibility only as out-of-pocket expenditure; when not reimbursed, only 10 % of the providers could significantly offer this intervention. Availability of trastuzumab biosimilars was reported in more than a half of the responders (n = 107). Conclusion: Stark disparities are reported, with high out-of-pocket expenses for HER2 testing and significant financial barriers to access trastuzumab treatments. Policy solutions are urgently warranted for the selection, prioritization, and reimbursement of essential health interventions, to result in improved population health. Policy summary statement: the inclusion of essential services for cancer management should be assured and financed in the benefit packages of healthcare to all. Prioritizing high-value health interventions, including medicines and medical devices, is critical to deliver impactful programs on population health.